Pemanfaatan Media Interaktif Sebagai Sarana Pembelajaran Efektif Di Era Digital - Mailizar; Ghina Annisa; Yuan Andinny (CV. Multi Kreasi Media, 2025)
The rapid development of digital technology has a significant impact on various aspects of life, including the world of education. In this digital era, conventional learning methods that only rely on face-to-face delivery of materials and the use of textbooks as the main source are considered less effective to meet the increasingly dynamic learning needs of students. The current generation, often referred to as